MANFAAT MEDIA PEMBELAJARAN DALAM PROSES BELAJAR DAN MENGAJAR MAHASISWA DI PERGURUAN TINGGI - Istiqlal, Abdul (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2018)
The purpose of this research was to know the benefits of using media in learning and teaching process for students in university, especially at STKIP Ahlussunnah Buktitinggi. This research used qualitative research and descriptive method. The result of this research explained that using media in learning and teaching process for students in university is very useful. The media distributed information from the informant (lecturer) to the receiver (student). Media in learning and teaching process as message deliverer technology (information) could use to teaching needs or physic tool to deliver learning subject. From this research was found that the benefits of media were to make the interaction between lecturer and students went smoothly and to help the students learned optimally.